Department of Medicine Local Area Network: A Strategic Solution for the 1990's - Price, Ronald N. (1989)
In 1986 the Department of Medicine at Loyola University Medical Center (LUMC) Chicago chose local area network technology (LAN) for implementing an integrated departmental health care computing system. LAN technology was selected for its: 1) low cost; 2) flexibility/adaptability in system design; and, 3) wealth of end user software. The departmental network (MED-LAN) consists of six LANs, running Novell Netware 2.1 on Intel 80386 microcomputer file servers, with 75 nodes and 120 users. Each LAN encompasses one or more buildings and is internetworked through a campus-wide ethernet. These LANs provide access to applications such as electronic mail, wordprocessing, spreadsheet, database management and statistics. The Section of Medical Informatics has developed over 40 integrated applications utilizing distributed data management techniques that include: 1) new patient appointment system (14,000 patients annually); 2) patient charge capturing system; 3) clinical research databases; and, 4) patient management systems. To date MED-LAN has proven to be flexible and efficient in meeting the department's informational needs.